Exploring the Effectiveness of Urban Regeneration: The Comparative Study of the Industrial Heritage Sites of Łódź (Poland) and Yazd (Iran) - Dehghan Pour Farashah, Mohammadhossein; Niemczewska, Zdzisława Elżbieta; Porfírio Coutinho Guimarães , Pedro (European Journal of Geography, 2025)
To establish appropriate strategies for the urban regeneration of districts with industrial heritage, it is essential to consider the factors that may influence the effectiveness of any regeneration. This study compares the revitalisation of industrial heritage sites in Łódź, Poland, as a European regeneration model, and Yazd, Iran, as an Asian counterpart—two cities that share similar textile manufacturing histories but possess distinct political, cultural, and socio-economic factors. The study examines the challenges associated with achieving effective urban regeneration in the setting of industrial heritage sites. The study employed semi-structured interviews with experts and professionals, complemented by fieldwork and observational analyses of textile manufacturing heritage sites, with a particular emphasis on revitalisation projects. The originality of this paper lies in the application of a synthetic approach to the analysis of qualitative data for comparing typologies of urban regeneration strategies within the contexts of two socio-culturally and economically distinct countries. The results indicate that for effective urban regeneration within industrial heritage sites it necessitates the attainment of socio-economic outcomes through a balanced approach to public-private financing, while mitigating the undue influence of private investments. Furthermore, projects that enhance accessibility and infrastructure, as well as promote the adaptive reuse of historical resources, should be prioritised. Such initiatives not only generate financial income but also yield social benefits and contribute to the preservation of cultural heritage values. The paper provides valuable insights for urban planners regarding the effectiveness of urban regeneration processes in districts characterised by industrial heritage. Highlights: The revitalisation project must be designed to align with both material and non-material values. Shifts from private investments to collaboration highlight the industrial heritage in Łódź. Substantial evidence underscores the impact of religious values on urban management in Yazd.